Investigating the Role of Asbestos Exposure in the Development of Small Duct Intrahepatic Cholangiocarcinoma - Kadhim, Sajjad Jawad (American Journal of Biology and Natural Sciences, 2025)
Intrahepatic cholangiocarcinoma (iCCA) is an uncommon liver cancer that has recently been categorized into two morphological subtypes: small duct and large duct. Emerging evidence points to asbestos as a potential risk factor for iCCA; however, no prior studies have explored the association between asbestos exposure and iCCA subtypes. This study aimed to investigate the relationship between asbestos exposure and the morphological classification of iCCA. A total of 50 patients who underwent surgical resection for iCCA were prospectively enrolled. Asbestos exposure was evaluated using the standardized questionnaire from the patient of medical city of Baghdad. Histopathological analysis of the resected specimens identified 36 cases of small duct iCCA (sd-iCCA) and 14cases of large duct iCCA (ld-iCCA). Among the sd-iCCA group, five patients had confirmed or probable occupational exposure to asbestos, whereas none of the ld-iCCA cases were classified as occupationally exposed. Other forms of asbestos exposure—such as possible occupational, familial, or environmental—were documented in 15 sd-iCCA cases and 2 ld-iCCA cases. Notably, 12 sd-iCCA patients (33.3%) and 7 ld-iCCA patients (50.0%) were considered unlikely to have been exposed to asbestos. These findings suggest a stronger association between asbestos exposure and the small duct subtype of iCCA, implying that asbestos fibers may act as a parenchymal rather than ductal carcinogenic factor. As this is a preliminary investigation, further validation through case-control studies or larger independent cohorts is warranted.